Men of the people? Democracy and prebendalism in Nigeria's Fourth Republic National Assembly. Issue 4 (19th May 2021) - Demarest, Leila
ABSTRACT: While Nigeria's National Assembly has become increasingly assertive since the start of the Fourth Republic, lawmakers continue to be heavily engaged in corruption. Such rent-seeking practices are commonly regarded as antithetical to democratization. In this article, however, I argue that individual access to public rents actually supports legislative independence. Based on an original dataset of 8th National Assembly MPs (2015–2019), I find that membership of lucrative committees is positively associated to the number of bills and motions sponsored. I also show that while legislative initiatives may be self-serving, an important share also appear to strengthen accountability and the rule of law. This result can be explained by the fact that MPs access to rents is not determined by their loyalty towards the president, but rather by their relations with the Assembly leadership and the bureaucracy. Increased monetary power in turn strengthens lawmakers to play a more independent role in politics.